Programmable ferroelectric tunnel memristor - Quindeau, Andy; Hesse, Dietrich; Alexe, Marin (Frontiers in Physics, 2014)
We report a programmable analog memristor based on genuine electronic resistive switching combining ferroelectric switching and electron tunneling. The tunnel current through an 8 unit cell thick epitaxial Pb(Zr0.2Ti0.8)O3 film sandwiched between La0.7Sr0.3MnO3 and cobalt electrodes obeys the Kolmogorov-Avrami-Ishibashi model for bidimensional growth with a characteristic switching time in the order of 10−7 s. The analytical description of switching kinetics allows us to develop a characteristic transfer function that has only one parameter viz. the characteristic switching time and fully predicts the resistive states of this type of memristor.